1996
DOI: 10.1073/pnas.93.3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Plasmodium falciparum malaria parasites by homologous integration of plasmids that confer resistance to pyrimethamine.

Abstract: Plasmodium falciparum malaria parasites were transformed with plasmids containing P. falciparum or Toxoplasma gondii dihydrofolate reductase-thymidylate synthase (dhfr-ts) coding sequences that confer resistance to pyrimethamine. Under pyrimethamine pressure, transformed parasites were obtained that maintained the transfected plasmids as unrearranged episomes for several weeks. These parasite populations were replaced after 2 to 3 months by parasites that had incorporated the transfected DNA into nuclear chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
261
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(266 citation statements)
references
References 29 publications
(13 reference statements)
3
261
0
2
Order By: Relevance
“…3D7 ring-stage parasites were transfected with 50 g of each plasmid using low voltage electroporation conditions (27), and resistant parasites were selected with 100 nM pyrimethamine. To enrich the population for parasites containing plasmid integrated into the DPAP1 locus, two rounds of drug cycling were carried out during which parasite cultures were grown for 21 days in the absence of drug to allow loss of the episome followed by reapplication of drug pressure (28).…”
Section: Methodsmentioning
confidence: 99%
“…3D7 ring-stage parasites were transfected with 50 g of each plasmid using low voltage electroporation conditions (27), and resistant parasites were selected with 100 nM pyrimethamine. To enrich the population for parasites containing plasmid integrated into the DPAP1 locus, two rounds of drug cycling were carried out during which parasite cultures were grown for 21 days in the absence of drug to allow loss of the episome followed by reapplication of drug pressure (28).…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, our knowledge of the molecular interactions between host and parasite during this stage of infection was limited due to the small number of sporozoites and EEFs present in the mammalian host and to the lack of an in vitro system for growing sporozoites. With the sequencing of the human and rodent malaria parasite genomes [1,2] as well as advances in transfection [3][4][5] and intravital microscopy [6], our knowledge of these stages has increased dramatically. Here we summarize what is currently known about the interaction between Plasmodium sporozoites and their mammalian host, beginning with sporozoite injection into the dermis and ending with invasion of their target, the hepatocyte.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is now established that mutations occurring at key positions in pfcrt and dhfr genes and, to a lesser extent, dhps gene, are highly correlated with the in vitro response of P. falciparum to the corresponding drugs. [3][4][5][6] The genetic mechanism of resistance to amino alcohols and artemisinin derivatives has not been totally elucidated. The results of several studies, mostly involving laboratory-adapted P. falciparum strains that were subjected to in vitro drug pressure, have suggested that amplification of pfmdr1 may be associated with resistance to chloroquine and/or amino alcohol drugs.…”
Section: Introductionmentioning
confidence: 99%